Effect of Job Demand and Personal Resource on Employee Work Engagement with Burnout as a Mediating Variable - Ratri, Dina Rahayuning; Budiono, Nur Aktif (Dinasti Publisher, 2023)
This study aims to examine the impact of Job Demand and personal resources on employees' Work Engagement at PT Pegadaian Head Office, with Burnout as a mediator. The researchers used a quantitative approach and hypothesis testing to investigate the relationships between independent variables (Job Demand and personal resources) and the dependent variable (Work Engagement) using the Partial Least Square-Structural Equation Model. They distributed questionnaires to 267 employees out of a total of 792 working at PT Pegadaian Head Office. Four out of seven hypotheses in this study were confirmed and accepted. The findings indicated that Job Demand and personal resources have a significant and positive direct influence on Work Engagement. However, the direct impact of personal resources on Work Engagement was not found to be significant. Interestingly, the study also revealed that Burnout acts as a mediator between personal resources and Work Engagement. In conclusion, this research sheds light on the interplay of Job Demand, personal resources, Burnout, and Work Engagement among employees at PT Pegadaian Head Office.